The Representation of White Matter in the Central Nervous System - Baud, Robert; Sprumont, Pierre; ten Donkelaar, Hans J. (Frontiers in Neuroanatomy, 2018)
The white matter of the central nervous system (CNS) is difficult to represent in anatomy because it is located predominantly “between” other anatomical entities. In a classic presentation, like a cross section of a brain segment, white matter is present and can be labeled adequately. Several appearances of the same entity are feasible on distant presentations. The problem is the absence of a global view on long tracts, and more generally, the lack of a comprehensive classification of white matter pathways. During the recent revision of the Terminologia Anatomica (TA, 1998), in particular the chapter on the nervous system, resulting in the Terminologia Neuroanatomica (TNA, 2017), the authors have developed a new schema for the representation of white matter. In this approach, white matter is directly attached to the CNS, and no more considered as part of the brain segments. Such a move does not affect the content but redistributes the anatomical entities in a more natural fashion. This paper gives an overall description of this new schema of representation and emphasizes the benefits. The new classification of white matter tracts is developed, selecting the origin as the primary criterion and the type of tract as the secondary criterion.